Perception of corruption and the fi ght against corruption in the Republic of Croatia - Zoran Malenica; Ranka Jeknić (Zbornik Radova Pravnog Fakulteta u Splitu, 2010)
Starting from the institutional and financial assumptions of the fight against corruption, and review of results on the fight against corruption, including statistics on court cases and convictions related to the area over the past seven years, the paper analyzes some of the results of the relevant researches about the perception of corruption in Croatia, with emphasis on data relating to perception of corruption and the degree of (dis)trust in institutions from the research project “Social stratification and value orientations in the Croatian society” in 2010.